The legibility of urban square in shaping city image of historical cities in Peninsular Malaysia / Zulkefle Ayob, Siti Norlizaiha Harun - Ayob, Zulkefle; Harun, Siti Norlizaiha (2012)
The "padang" or square was one of the most notable features of British Colonial towns. This research attempt to prove that the padang can be a strong element in shaping the image of the cities. Historic cities of Kuala Lumpur, Penang and Malacca were chosen as case study sites for their similar characters, uniqueness and importance. The aim and objectives of this research is to study and examine the character of urban squares in historic cities in Malaysia and to find its contributions in shaping the city's image. The deductive study and literature formed the hypothesis of this research that is: the legibility of Urban Square in shaping city image does not stand on its own, but because of strong character of surrounding elements. This mixed-methodology researchcombined literature review, case study, and cognitive methods. It applied qualitative approach in collecting and interpreting data and quantitative approach in the analysis. Data collection to this research is divided in three methods namely Literature Review, Case Study and Interpretation Survey on Image. The findings concluded that all the elements remembered and memorized are the distinctive associated qualities in the image of a place therefore contributing to city image